Performance, beef quality and expression of lipogenic genes in young bulls fed low-fat dried distillers grains. (February 2020) - Reis, Viviane Amin; Reis, Ricardo Andrade; Araújo, Tiago Luís Da Ros de; Lage, Josiane Fonseca; Teixeira, Priscilla Dutra; Gionbelli, Tathyane Ramalho Santos; Lanna, Dante Pazzanese; Ladeira, Marcio Machado
Abstract: Two studies were carried out, the first with the objective to evaluate performance, beef quality and expression of genes involved in lipid metabolism in the muscle of bulls fed with or without low-fat dried distillers grains with solubles (DDGS, 21% DM) in the diet. In the second, eight rumen-fistulated bulls were assigned in a switch back design to evaluate the fatty acid profile of omasal fluid. We hypothesized that bulls fed DDGS may have an improved fatty acid profile and expression of genes involved in lipid metabolism may be altered, without affecting performance. Bulls fed DDGS had greater ( P < .05) concentrations of PUFA n-6 in the omasum and muscle. CLA t10, c12 content was higher and there was lower expression of the LPL gene ( P = .05) in the muscle of animals fed DDGS ( P = .03). In conclusion, DDGS can be used as a protein feedstuff because it maintains beef quality.